2011
DOI: 10.1007/s10147-011-0217-3
|View full text |Cite
|
Sign up to set email alerts
|

A novel hyperthermia treatment for bone metastases using magnetic materials

Abstract: Patients with bone metastases in the extremities sometimes require surgical intervention to prevent deterioration of quality of life due to a pathological fracture. The use of localized radiotherapy combined with surgical reinforcement has been a gold standard for the treatment of bone metastases. However, radiotherapy sometimes induces soft tissue damage, including muscle induration and joint contracture. Moreover, cancer cells are not always radiosensitive. Hyperthermia has been studied since the 1940s using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
67
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(73 citation statements)
references
References 37 publications
2
67
0
4
Order By: Relevance
“…Matsumine et al reported a novel MNHT system for patients with bone metastases in their extremities [85]. They used a calcium phosphate cement containing MNPs.…”
Section: Clinical Trials Of Mnht Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Matsumine et al reported a novel MNHT system for patients with bone metastases in their extremities [85]. They used a calcium phosphate cement containing MNPs.…”
Section: Clinical Trials Of Mnht Treatmentmentioning
confidence: 99%
“…The development of AMF applicators is also an important issue for applying MNHT to various forms of cancers with different sizes, shapes and locations. While significant progress has been made[23,78,85,87], more sophisticated applicators may still need to be developed. In addition, the development of noninvasive thermometry that accurately measures or estimates the temperature distribution in situ within and outside tumor tissues during MNHT treatment also needs to be developed, as reviewed byKaddi et al …”
mentioning
confidence: 99%
“…Firstly, the cancer-affected region is extirpated by surgery and the excision site is sometimes filled with injectable calcium phosphate cement in order to achieve early postoperative ambulation [2][3][4]. After the surgical operation, chemotherapy is performed in order to prevent cancer recurrence and metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…Matsumine et al [65] developed an injectable calcium phosphate cement containing MNPs for patients with bone metastases in the extremities. Calcium phosphate cement containing MNPs was injected to fill the bone defect following resection of bone tumors, and AMF was applied totally 10 times from day 8 to day 29 after surgical operation for 23 patients with 25 bone metastases.…”
Section: Clinical Trials For Mnhtmentioning
confidence: 99%